Finance For Growth and Policy Options for Emerging and Developing Economies: The Case of Nigeria - Olayiwola, Wumi; Okodua, Henry; Osabuohien, Evans S (Asian Development Policy Review, 2015)
Finance is generally regarded as important for economic growth, but the role of finance in economic growth is a controversial issue in the economic literature. The concept of “finance for growth” refocuses the relationship between finance and economic growth by redirecting the role of government policies in finance, and recognizes how finance without frontiers is changing what government policies can do and achieve. The focus of this paper is not to join the debate, nor to analyse the impact of financial development on economic growth, but to discuss the concept of “finance for growth” within the context of emerging and developing economies. The increasing development needs of Emerging Market Economies (EMEs) to raise per capita income, reduce unemployment rate, construct and maintain basic infrastructure, and invest more in human capital, make the role of finance for growth in these economies indispensable. The paper reviews the financial policies in selected EMEs including: China, South Africa and Nigeria and attempts to situate the Nigerian economy among the EMEs within the context of Finance for Growth. The paper notes that financial policies designed in various EMEs had the similar goal of making the financial system to provide key financial functions. However, large differences exist in the efficiency of the financial system in each country. The paper found that what matters to economic growth is access to financial services or financial inclusion and not which sector supplies the funds. The paper suggests appropriate policy options to build confidence in the Nigerian financial system.